Efektivitas Pelayanan Badan Penyelenggara Jaminan Sosial Kesehatan Di Mal Pelayanan Publik Kabupaten Sleman - Fikrin; Wardani, Fera Arista; Afrendi, Baselius; Ferianto, Agus (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2023)
The purpose this study aims to determine the effectiveness of the services of the Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan in the Sleman District Public Service Mall. This type of research is a qualitative descriptive study with data collection techniques namely, interviews, observation, and documentation. Public demand for good governance has a real effect on the government. The real manifestation of these demands is the establishment of a fast, responsive, accurate, and transparent public service. The Sleman Regency Public Service Mall is one of the concrete manifestations of the Regional Government in realizing good governance. One of the services facilitated at the Sleman Regency Public Service Mall is Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan service. This study concluded that the existence of the Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan services in the MPP Sleman was not effective in serving the community.